Medical Emergency in Orthodontics: A Case Report of Buccal Space Infection - Dodda, Kiran Kumar; Khan, Mohammadi Begum (Journal of Orofacial Research, 2014)
Introduction: Orthodontic appliances or parts of fixed Orthodontic appliances can occasionally cause problems for the patients and orthodontists. These problems could range fromminor discomfort to severe spread of the infection due to soft tissue injury leading to secondary space infections, which need an immediate medical attention and prompt emergency care. Case report: A case of 19-year-old female patient is presented to show the involvement of medical assistance to treat buccal space infection which was secondary to the traumatic ulcer caused by the constant maxillary molar tube injury to right sided cheek mucosa. Discussion: The spaces of the head and neck can allow the spread of the infection from the teeth and the associated oral tissues because the pathogens can travel within the facial planes, by the spread of the related inflammatory exudates. When involved in infections, the space can undergo cellulitis, which can cause a change in the normal proportions of the face. Conclusion: These emergency conditions need the medical and surgical intervention to provide relief to the patient and prevent the spread of the infection into the jaw bone, which could lead to osteomyelitis and other severe problems.